Agentes causales de micosis superficiales en pacientes diabéticos que acuden al laboratorio Biolab del cantón Yantzaza - Sarango Campoverde, Nixon Ovidio (2015)
Pathogenic fungi are commonly found in the environment and are part of the flora of the human being, which is continually exposed to various types of microorganisms. These agents take advantage of the presence of factors such as wet-tropical weather conditions, subjects presenting superficial tissue trauma, having inadequate hygiene habits that are immunocompromised or who have chronic diseases such as diabetes mellitus, to produce fungal infections. Diabetes is a disease that will continue to increase and affecting much of the population, which if not controlled properly the patient is prone to diseases like superficial mycosis that affects keratinized tissues. This research entitled "causative agents of superficial mycoses in diabetic patients attending the Canton Laboratory BIOLAB Yantzaza" in the period March to July 2013, were to: identify fungal structures in superficial lesions of diabetic patients Yantzaza Canton; determine which species are most prevalent dermatophyte that affects skin, nails and hair; develop and implement preventive educational proposal to diabetic patients attending the clinical microbiology laboratory BIOLAB, was conducted by a cross-sectional study that consisted of 50 diabetic patients with fungal lesions, skin and nail samples were obtained limb upper and lower, for the identification and cultivation technique applied micro culture reaching the following results, 76% of the 50 samples tested were positive for ringworm, of which the T. rub rum was the most prevalent species in surface mycosis diabetic patients with 47.37%, followed by T. mentagrophytes with 39.47% and 13.16% E. floccose finally diabetics was reported as prevent reinfection of fungal diseases by an educational talk. Keywords: ringworm, dermatophytes, ringworm, diabetes mellitus, culture.